Role of Individual Academics and International Universities in Health Research in Nepal (Nepal Journal of Epidemiology, 2012)
Nepal has made progress in health sciences and medical education over the past decade. We believe that there is a need in Nepal for a greater research emphasis on mixed-methods approaches, qualitative research, critical appraisal & systematic reviewing and health economics. Specifically to the discipline of epidemiology, Nepal should consider establishing more and better epidemiological studies, the kind of population-based studies that can identify risk factors, track changes over time at a population level over the decades to come.  We know how important such long-term research is but we are also painfully aware how expensive this kind on long-term research can be.DOI: http://dx.doi.org/10.3126/nje.v2i2.6572 Nepal Journal of Epidemiology 2012;2(2):179-81